2005
DOI: 10.1128/jb.187.1.45-53.2005
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Diffusion of Phosphorylated CheY through the Cytoplasm of Escherichia coli

Abstract: Many aspects of the biochemistry and physiology of living cells have in the past been simulated by networks of reactions as though they were electronic circuits. In such studies, components such as receptors, enzymes, or metabolites are portrayed as being wired together in a spatially defined manner through enzymatic and other reactions. But it is clear that living circuitry is not like this; it has unique features such as a highly malleable internal architecture and the existence of a multitude of molecular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
156
0
2

Year Published

2009
2009
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(167 citation statements)
references
References 34 publications
9
156
0
2
Order By: Relevance
“…Previous studies have concluded that the localization of the phosphatase, CheZ, to the polar cluster, minimizes the formation of spatial gradients of CheY P along the length of the cell (Vaknin and Berg, 2004;Lipkow et al, 2005). In line with these studies, our model predicts that outside the polar regions there is a uniform concentration of free CheY P along the length of the cell.…”
Section: Spatial Distribution Of Chey In Wild-type Cellssupporting
confidence: 85%
“…Previous studies have concluded that the localization of the phosphatase, CheZ, to the polar cluster, minimizes the formation of spatial gradients of CheY P along the length of the cell (Vaknin and Berg, 2004;Lipkow et al, 2005). In line with these studies, our model predicts that outside the polar regions there is a uniform concentration of free CheY P along the length of the cell.…”
Section: Spatial Distribution Of Chey In Wild-type Cellssupporting
confidence: 85%
“…Although these simulation results are coherent and in agreement with 2D simulations [36][37][38][39][40][41][44][45][46][47] , there are experimental 3D studies 31,35 that show a reverse result for the limiting diffusion coefficient and the anomalous diffusion exponent values.…”
Section: I) Effect Of Obstacle Density and Sizesupporting
confidence: 80%
“…Lipkow and his coworkers 46 have developed a computational program, Smoldyn, for studying cellular molecular processes taking into account both the spatial location of proteins (and their complexes) and their diffusive motion. This program has shown results in good agreement with experimental data for diffusion of signaling protein CheYp through the cell.…”
Section: Introductionmentioning
confidence: 99%
“…In a simple system in which kinase molecules are phosphorylated at the cell membrane and dephosphorylated by a phosphatase molecules located homogeneously in the cell cytosol (analyzed by Brown and Kholodenko 1999) small diffusion implies high gradient and low kinase activity in the cell center. The problem of receptor-kinase interaction has been also studied in the context of diffusion with obstacles in the stochastic numerical simulations of bacterial chemotaxis (Lipkow et al 2005). One of the conclusions of Lipkow et al 2005 is that crowding results in a fall of the apparent diffusion coefficient and at the anterior end, where CheY is phosphorylated, the local concentration of CheYp increases and therefore accelerates the response of the anterior close motor.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of receptor-kinase interaction has been also studied in the context of diffusion with obstacles in the stochastic numerical simulations of bacterial chemotaxis (Lipkow et al 2005). One of the conclusions of Lipkow et al 2005 is that crowding results in a fall of the apparent diffusion coefficient and at the anterior end, where CheY is phosphorylated, the local concentration of CheYp increases and therefore accelerates the response of the anterior close motor. At the other, posterior, end of the cell, the local CheYp concentration is reduced by the need to diffuse through the obstacles and the responses of motors in this region is consequently delayed.…”
Section: Introductionmentioning
confidence: 99%